Efficient Use of Energy Resources of the Generator of Hot Gases in the Thermal Preparation of Motor Vehicles - Nigmatullin, Shamil; Gabitov, Ildar; Izmailov, Andrey; Negovora, Andrei; Samikov, Ruslan; Razyapov, Mahmut (International Journal of Energy Economics and Policy, 2019)
Generators of hot gases (GHG) are used for thermal preparation of vehicles in cold climatic conditions. Their wide use is caused by the high thermal power and safety of application. The heat released in burning zone is used partly for heating air flow, partly for heating of GHG parts: guide nozzle and the false pallet. The generator of hot gases consumes from 70 to 150 W of the car battery power. In the process of thermal preparation, this leads to a decrease in the battery capacity, and as a result - the impossibility of starting the motor of the vehicle. The issue of reducing the energy consumption of the GHG, without changing its consumer qualities, becomes urgent. Keywords: thermal preparation, generator of hot gases, guide nozzle, thermoelectric generator, losses of thermal energy, the temperature field, fillers JEL Classifications: O13, Q40 DOI: https://doi.org/10.32479/ijeep.8503